A meta-synthesis study of the key elements involved in childhood vaccine hesitancy - Díaz Crescitelli, M. E.; Ghirotto, L.; Sisson, H.; Sarli, L.; Artioli, G.; Bassi, M. C.; Appicciutoli, G.; Hayter, M. (Public Health, 2020)
Objectives: Immunization is one of the most successful and cost-effective interventions to improve health outcomes. However, internationally, the phenomenon of parental vaccine hesitancy is increasing and presents a growing challenge for health professionals. This article summarizes the evidence surrounding childhood vaccine hesitancy from the perspective of parents. Study design: We conducted a systematic review and meta-synthesis of qualitative studies. Methods: We searched for qualitative research articles in electronic databases from inception to March 2018. In addition, a manual search of the retrieved articles and their references was conducted to identify other potential articles. We used the Critical Appraisal Skills Programme to examine study validity, adequacy and potential applicability of the results. No articles were excluded for reasons of quality. By performing a meta-synthesis, we identified descriptive themes and, subsequently, the conceptual elements of vaccine hesitancy. Results: The review included 27 studies involving a total of 1557 parents who were hesitant about vaccinating their child. Five overarching categories were identified: (1) risk conceptualization; (2) mistrust towards vaccine-related institutions, pharmaceutical companies, researchers, health professionals and the information from media; (3) parental alternative health beliefs about childhood immunity, vaccine scheduling and the perceived toxicity of vaccinations; (4) philosophical views on parental responsibility; and (5) parents' information levels about vaccination. Conclusions: Healthcare providers need to approach this difficult situation considering that parents desire to do what they feel right for the child. Understanding the core elements of hesitancy will allow health professionals to adopt effective communication and behavioural strategies.
Keywords: Childhood vaccination hesitancy; Parents; Meta-synthesis; Systematic review; Qualitative research; Health promotion